Toxicological effects resulting from co-exposure to nanomaterials and to a β-blocker pharmaceutical drug in the non-target macrophyte species Lemna minor. (1st April 2023) - Silva, Paula Mayara Morais da; Alkimin, Gilberto Dias de; Camparotto, Natália Gabriele; Prediger, Patricia; Nunes, Bruno
Abstract: The wide use of carbon-based materials for various purposes leads to their discharge in the aquatic systems, and simultaneous occurrence with other environmental contaminants, such as pharmaceutical drugs. This co-occurrence can adversely affect exposed aquatic organisms. Up to now, few studies have considered the simultaneous toxicity of nanomaterials, and organic contaminants, including pharmaceutical drugs, towards aquatic plants. Thus, this study aimed to assess the toxic effects of the co-exposure of propranolol (PRO), and nanomaterials based on cellulose nanocrystal, and graphene oxide in the aquatic macrophyte Lemna minor . The observed effects included reduction of growth rate in 13% in co-exposure 1 (nanomaterials + PRO 5 μg L −1 ), and 52–64% in co-exposure 2 (nanomaterials + PRO 51.3 mg L −1 ), fresh weight reduction of 94–97% in co-exposure 2 compared to control group, and increased pigment production caused by co-exposure treatments. The analysis of PCA showed that co-exposure 1 (nanomaterials + PRO 5 μg L −1 ) positively affected growth, and fresh weight, and co-exposure 2 positively affected pigments content. The results suggested that the presence of nanomaterials enhanced the overall toxicity of PRO, exerting deleterious effects in the freshwater plant L. minor, suggesting that this higher toxicity resulting from co-exposure was a consequence of the interaction between nanomaterials and PRO. Graphical abstract: Image 1 Highlights: CNC and GO nanomaterials did not compromise growth and fresh weight of plants. Nanomaterials triggered the antioxidant system of plants. The co-exposure of propranolol with CNC/GO impaired plant growth and fresh weight. Propranolol/nanomaterials complexes increased pigment contents. PRO was adsorbed by nanomaterials and fully desorbed after 24 h.